Frequency of Poisoning Leading to Hospitalization in the Intensive Care Units in Northeastern Iran, 2008-2018 - Mohammad Shokrzadeh; Danial Jafari; Reza Hoseinpoor; Azam Delaram; Akram Pouyan Sadr; Elham Masodi; Mehrnosh Deylami; Gholamali Lashkarboloki; Yaghoub Shayeste; Narges Fatemi (Golestan University of Medical Sciences, 2021)
Background: Poisoning is a common cause of hospitalization in intensive care units (ICU). The present study aimed to investigate   the frequency of poisoning leading to hospitalization in the intensive care units of an educational hospital, Golestan University of Medical Sciences, in Gorgan in 2008-2018. Methods: This cross-sectional study conducted on patients with acute poisoning admitted to the ICUs of 5 Azar Hospital in Gorgan from 20 March 2008, to 20 March 2018. We collected data from all patientschr('39') medical record using a checklist.  Data was presented in proportions, mean and standard deviation. Results: All of 631 patients with poisoning were admitted to the ICUs were male (61.3%) and 40.3% were in the age range of 20-29 years. The mean length of hospital stay in the ICU was 4.21±3.45 days. The most common type and cause of poisoning were suicide attempt (65.3%) and drugs (65.6%), respectively. The common drugs were used including the benzodiazepines (38.9%) and narcotic drugs (18.6%). The rate of death of poisoning was 11.1%, of which 44.3% was due to aluminum phosphide. Conclusion: Benzodiazepines and aluminum phosphide were the most common causes of poisoning and death due to poisoning in the ICU. Due to the high mortality rate, it seems necessary to provide more education and information via the media, especially in the field of aluminum phosphide hazards.